Screening for low muscularity in colorectal cancer patients: a valid, clinic‐friendly approach that predicts mortality. Issue 5 (31st July 2018) - Cespedes Feliciano, Elizabeth M.; Avrutin, Egor; Caan, Bette J.; Boroian, Adam; Mourtzakis, Marina
Abstract: Background: Low skeletal muscle quantified using computed tomography (CT) scans is associated with morbidity and mortality among cancer patients. However, existing methods to assess skeletal muscle from CT are time‐consuming, expensive, and require training. Clinic‐friendly tools to screen for low skeletal muscle in cancer patients are urgently needed. Methods: We included 807 scans from non‐metastatic colorectal cancer patients. With the digital ruler available in most radiological software, we implemented an abbreviated method to assess skeletal muscle area at the third lumbar vertebra (L3), which consisted of assessing the height and width of the psoas and paraspinal muscles and computing their combined 'linear area' in centimetres squared (cm 2 ). A subset of CT scans was assessed twice by two analysts to compute intra‐rater and inter‐rater reliability. We derived cut‐points for 'low' linear area using optimal stratification and then calculated the sensitivity and specificity of these cut‐points relative to standard methods (total L3 cross‐sectional area assessed with Slice‐O‐Matic research software). We further evaluated the association of low linear area with death from any cause after colorectal cancer diagnosis in Cox proportional hazards models adjusting for demographics, smoking, body mass index category, and tumour characteristics. Results: The linear area was highly correlated with total cross‐sectional area assessed using standard methods [ r = 0.92; 95% confidence interval (CI): 0.91, 0.93] overall and within subgroups defined by age, sex, and body mass index group. Intra‐rater and inter‐rater reliability were equally high (both intra‐class correlations = 0.98). Cut‐points for low linear area were sensitive (0.75; 95% CI: 0.70, 0.80) and specific (0.77; 95% CI: 0.73, 0.80) for identifying low skeletal muscle relative to the standard of total L3 cross‐sectional area. The hazard ratio and 95% CI for death associated with a low linear area were hazard ratio = 1.66; 95% CI: 1.22, 2.25. Conclusions: Clinic‐friendly methods that assess linear area from CT scans are an accurate screening tool to identify low skeletal muscle among non‐metastatic colorectal cancer patients. These linear measures are associated with mortality after colorectal cancer, suggesting they could be clinically useful both to improve prognostication and to provide a practical screening tool to identify cancer patients who require nutrition or exercise intervention.